Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Pakoakuina Motorcycle Karawang - Muhamad Elki Purnama; Sungkono Sungkono; Maman Mulya Karnama (Jurnal Syntax Admiration, 2024)
The investigation was conducted with a focus on seeing how two factors, namely “work environment and work motivation”, affect employee work results at PT Pakoakuina Motorcycle. To attain this objective, the researcher utilized a purposive sampling technique, which means that the employees selected to serve as respondents were specifically chosen based on certain criteria relevant to the research. A total of 35 employees from PT Pakoakuina Motorcycle were involved as respondents by answering the distributed surveys. The gathered data were subsequently examined with the  SEM PLS method. The findings of the analysis show that the work environment has a significant influence on employee performance, meaning that environmental conditions in the workplace, such as facilities, atmosphere, and relationships between employees, greatly affect employee productivity and work performance. On the other hand, the results of the analysis also show that work motivation does not have a significant influence on employee performance. This shows that although work motivation exists among employees, it does not always translate into improved employee performance within PT Pakoakuina Motorcycle